NILAI BUDAYA YANG TERCERMIN DALAM CERITA SAMAHU LABUR DI DESA BAGAK KABUPATEN LANDAK - Eliska Winda; Parlindungan Nadeak; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims and is motivated by the idea of analyzing and interpreting data on cultural values that are reflected in the story of Samahu Labur in Bagak village, Menyuke sub-district, Landak district. The problem in this study is how the cultural values are reflected in the folklore of Samahu Labur, Dayak Kanayatn oral literature in Bagak village, Menyuke sub-district, Landak district. The research method used is descriptive, the form of qualitative research and the approach used is the sociology of literature. The source of data in this study is the text of the folklore Samahu Labur. Data collection techniques are observation techniques (direct observation), interview techniques, documentation techniques, recording techniques, and recording techniques. The results of the analysis of research data show that there are three cultural values that are reflected in the folklore of Samahu Labur, namely cultural values that reflect the human relationship with God manifested in the form of trust, gratitude and worship, cultural values that reflect the relationship between humans and humans are manifested in the form of mutual cooperation, compassion and harmony and cultural values that reflect the relationship between humans and nature are manifested in the form of humans being friendly with nature. The folklore of Samahu Labur can be used as learning material in Senior High School class X in Basic Competence 3.7 identify the values and content contained in folklore orally and in writing and Basic Competence 4.7 retell folklore orally and in writing based on the 2013 curriculum for Indonesian subjects.